Zāļu iegādes izdevumu kompensācijas sistēmas problemātiskie aspekti. - Rubins, Andrejs (Latvijas Universitāte, 2012)
Darbā tiek pētīts zāļu kompensācijas tiesiskais regulējums Latvijā. Neskatoties uz to, ka zāļu kompensācija Latvijas mediju vidē tiek bieži apspriesta, ir tādi jautājumi, kuru atklāšanai ir būtiska nozīme pacientu tiesību nodrošināšanā. Darba pirmajā daļā autors sniedz vispārēju pārskatu par zāļu kompensācijas valsts politiku, normatīvo regulējumu un faktiski sniegto zāļu kompensācijas struktūru 2011.gadā. Darba otrajā daļā tiek analizēta kompensējamo zāļu A un B sarakstā iekļauto medikamentu kompensācijas atteikuma tiesiskā daba. Tiek pamatota hipotēze, ka kompensējamo zāļu A un B sarakstā iekļauto medikamentu kompensācijas atteikums ir publisko tiesību jomā un ir vērtējams kā faktiskā rīcība. Saskaņā ar šo teoriju nepieciešams nošķirt ārstniecības personas rīcību ārstniecības jomā, kas ir balstīta uz privātpersonu brīvu gribu un rīcību, kurai ir raksturīgs zināms valsts piespiedu elements. Darba trešajā daļā tiek pētīts jautājums par kompensējamo zāļu C sarakstā iekļauto medikamentu kompensācijas atteikumu tiesisko dabu un to atbilstību tiesību principiem. Tiek pamatota hipotēze, ka kompensējamo zāļu C sarakstā iekļauto medikamentu kompensācijas atteikums pamatojoties uz to, ka ir sasniegts noteikts pacientu skaits, nesamērīgi ierobežo pacientu tiesības uz veselību. Salīdzinājumam tiek analizēts līdzīgs regulējums veselības aprūpes jomā, kas ir vairāk saudzējošs pacientiem. Darba ceturtajā daļā tiek pētīts jautājums par zāļu kompensācijas atteikumu individuālajā kārtā tiesisko dabu un to atbilstību tiesību principiem. Tiek pamatota hipotēze, ka zāļu kompensācijas atteikums individuālajiem pacientiem, pamatojoties uz to, ka ir sasniegts individuālajām kompensācijām atvēlētais finansējums, nesamērīgi ierobežo pacientu tiesības uz veselību.

In this work the author analysed the legislation of medicine reimbursement in Latvia. The medicine reimbursement are often discussed in media environment of Latvia, despite this still are questions which are essential to clarify for patients to understand their rights. In the first section of this work the author provides a general overview of the state policy of the medicine reimbursement, legislation and structure of the medicine reimbursement in 2011. In the second section of this work the author analyzed the legal basis of refusal reimburse medicines which are included in the reimbursement lists A and B. The author defends the hypothesis, that denial of reimbursement of the medicine, which are included in reimbursement lists A and B, are in a scope of public law and should be viewed as the actual action in administrative law. According to this theory necessary separate actions of the medicine personnel as a treatment of the patients, which are based on free will of the parties’, from the actions of the medicine personnel by denial of reimbursement of the medicine included in reimbursement lists A and B, which have some coercive element of the State relations. In the third section of the work the author analyzed the legal nature of the issue of refusal of reimbursable medicine which are included in the reimbursement lists C and such refusal compliance with the principles of the law. The author defends hypothesis that refusal reimburse medicines on the ground of reason that were reached certain number of patients, which are declared by the State authority as a reimbursable, is disproportional and restricts patients' right to health. For the solution of the problem the author analyzes a similar legislation in the health care and proves that the state could introduce more respectful regulation for patients. In the fourth section of the work the author analyzed the legal nature of the issue when the State authority refuses to reimburse the medicine in an individual cases and such refusal compliance with the principles of the law. The author defends hypothesis, that the refuse reimburse the medicine in a individual cases on the ground of a reason that there were reached certain percentage of allowed funding for individual cases, in some cases could disproportionately restrict the patients' right to health. For the solution of the problem the author analyzes judgments and proves that there could be more respectful regulation for individual patients.
Problematic aspects of drugs reimbursement in Latvia.
Keywords: Juridiskā zinātne